Analisis Kinerja Pegawai melalui Pendekatan Balanced Scorecard pada Kantor Sekretariat Daerah Kota Depok - Astri Susana Maharani; Ignatius Jeffrey; Augustina Kurniasih (Telaah Bisnis, 2017)
This study aims to analyze the performance of employees through the Balanced Scorecard approach consisting of four perspectives: financial, customer, internal business processes, and learning and descriptive growth perspective. The method used is literature search on a budget document called Laporan Akuntabilitas Kinerja Pemerintah (LAKIP) or Government Performance Accountability Report, of Regional Secretariat office Depok in 2012-2013. The budget document was prepared in April 2014 for the financial perspective, while the other three perspectives were made through questionnaires completed by 30 respondents from the work partners of Regional Secretariat Office of Depok City. While the questionnaires for internal business process perspective, and learning and growth perspective were filled out by 129 respondents from the employee of Regional Secretariat Office of Depok City. These questionnaires were prepared within the period of March-September 2014. Likert scale was used for variable measurement where a score of 1 was the lowest value and the highest value was a score of 5. Hypothesis testing was done by assessing the results of the answers on the understanding of work partners and employees, by understanding the value of the percentage. The result showed that the performance of the financial perspective was very good, and the performance of employees through customer perspective indicated employees produce services in accordance with their duties and functions was also very good, which was showed by as much as 85.65% of respondents agreed. Moreover, the internal business process perspective showed employee produces services in accordance with the Standard Operating Procedure (SOP) as well as the result of learning and growth perspective were very good, with the results of as much as 89.14% and 91.59% of respondents agreed, respectively. These perspectives, hopefully will generate Balanced Scorecard framework that in turn, will provide inputs for the development of Human Resources (HR) at the office of the Regional Secretariat Depok.